The Role of the Kola Language in Wedding Ceremonies in Gumsey Village, Aru Islands Regency - Djabumona, Erlin Santhy; Pattiasina, Petrus Jacob; Lalapary, Heppy Leunard (Universitas Pattimura, 2022)
Based on this, the purpose of this study is to describe the function of Kola language in traditional wedding ceremonies in Gumsey Village, Sir-Sir Aru District, Aru Islands Regency. Kola language is a cultural language that is closely tied to the traditions of the community and is only used in customary contexts. Its use reflects not only communication but also cultural identity, values, and social cohesion. In traditional wedding ceremonies, the Kola language plays a crucial role in maintaining the sacredness of rituals and ensuring the continuity of ancestral heritage. This research was conducted using qualitative methods with data collection techniques such as interviews, recordings, and documentation. The findings show that the Kola language functions as a communication tool, a unifying medium, a means of self-expression, and a mechanism for social integration and adaptation within specific cultural situations. Furthermore, it serves as a tool for social control, guiding behavior and reinforcing communal norms. Preserving the Kola language is therefore essential for safeguarding the cultural life of the Moluccas community.